2021
DOI: 10.1001/jamanetworkopen.2021.11410
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Bitter Taste Receptor Phenotype and Clinical Outcomes Among Patients With COVID-19

Abstract: IMPORTANCE Bitter taste receptors (T2Rs) have been implicated in sinonasal innate immunity, and genetic variation conferred by allelic variants in T2R genes is associated with variation in upper respiratory tract pathogen susceptibility, symptoms, and outcomes. Bitter taste receptor phenotype appears to be associated with the clinical course and symptom duration of SARS-CoV-2 infection.OBJECTIVE To evaluate the association between T2R phenotype and patient clinical course after infection with SARS-CoV-2. DESIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“… ( Grimaudo et al, 2021 ) TAS2R38 Not mentioned USA 1935, 265 tested positive T2Rs may protect against illness by SARS-CoV-2. ( Barham et al, 2021 ) DDR1 rs17047200 Egypt 141 patients, 100 controls The AG genotype of the DDR1 rs4618569is associated with poor outcomes in COVID-19 patients. ( Agwa et al, 2021 ) TLR3 rs3775291 Spain and Italy N/A A missense mutation in TLR3 (rs3775291) is associated with severe disease.…”
Section: Discussionmentioning
confidence: 99%
“… ( Grimaudo et al, 2021 ) TAS2R38 Not mentioned USA 1935, 265 tested positive T2Rs may protect against illness by SARS-CoV-2. ( Barham et al, 2021 ) DDR1 rs17047200 Egypt 141 patients, 100 controls The AG genotype of the DDR1 rs4618569is associated with poor outcomes in COVID-19 patients. ( Agwa et al, 2021 ) TLR3 rs3775291 Spain and Italy N/A A missense mutation in TLR3 (rs3775291) is associated with severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be a result of different SARS-CoV-2 variants or differences in the genetic background of the population, as phenotypic expression of bitter taste receptors appeared to be associated with symptoms, immune response, clinical course, and recovery from COVID-19 infection. 33 Several studies in different countries have shown the long-term impact of COVID-19 on an individual's health. 34 Some research reported persistent symptoms extending beyond the period of initial illness or hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be a result of different SARS-CoV-2 variants or differences in the genetic background of the population, as phenotypic expression of bitter taste receptors appeared to be associated with symptoms, immune response, clinical course, and recovery from COVID-19 infection. 33 …”
Section: Discussionmentioning
confidence: 99%
“…This intronless taste receptor gene encodes a 7-transmembrane receptor protein, functioning as a bitter taste receptor [34]. Studies have shown that individuals who reported experiencing weak or no bitter tastes were considerably more likely to test positive for COVID-19, to be hospitalized, and to be symptomatic for a longer duration [35]. In addition, recent studies have been conducted that reduced TAS2R expression may influence the response to Chloroquine.…”
Section: Resultsmentioning
confidence: 99%